A systematic review on how primary care electronic medical record data have been used for antimicrobial stewardship - Ron Cheah; Caroline Chen; Daniel Capurro; Jo-Anne Manski-Nankervis; Vlada Rozova; Karin Thursky (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract